TEKNIK STEGANOGRAFI MENGGUNAKAN TRANSFORMASI SLANT DENGAN ALGORITMA ENKRIPSI ELGAMAL - Bagus S, I Gusti Agung; Sianipar21, Rismon H.; Wiryajati, I Ketut (DIELEKTRIKA, 2014)
Steganography Techniques is a technique that discusses how a message is inserted into a media file so that the third party was not aware of the message. By exploiting the limitations of the human sensory systems such as the eyes and ears, steganography method is applicable to a variety of digital media. The output of steganography has a same form perseption of the original, but the perception is limited to the ability of the human senses, not by a computer or other digital processing devices. To strengthen the security of the message, steganography techniques can be combined with other techniques such as cryptography and transformation. In this study, ElGamal cryptosystem used as a function to encode the message before it is sent and Slant Transformation as a function to scramble the image before the inserted message. The secret message was originally encrypted using ElGamal algorithm then pasted the image that has been transformed using a Slant transformation. The results of the images that have been inserted message, returned again to the original image, so the message has been inserted become invisible (hidden).